Characterization of Bacillus subtilis Bacteriophages - Brodetsky, Anna M. (1965)
Brodetsky, Anna M. (University of California, Los Angeles), and W. R. Romig. Characterization of Bacillus subtilis bacteriophages. J. Bacteriol. 90:1655–1663. 1965.—A group of six phages, SP5, SP6, SP7, SP8, SP9, and SP13, which use the Marburg strain of Bacillus subtilis as host was characterized. These phages, referred to as group 1, were examined for the following properties: host range, plaque morphology, stability, adsorption kinetics, one-step growth characteristics, calcium requirements, serum neutralization, thermal inactivation, and inactivation by ultraviolet irradiation. Five unrelated B. subtilis phages, SP3, SP10, PBS1, SP alpha, and SP beta, were included in the studies. When first isolated, none of the group 1 phages was able to replicate efficiently on B. subtilis SB19, a mutant of the “transforming” B. subtilis 168. Host range mutants capable of growth in SB19 were isolated for all of the group 1 phages except SP13, and are designated the “star” phages (SP5* through SP9*). For characterization, SB19 was used as host for the star phages, and another B. subtilis mutant, 168B, was host for SP13.